Antioxidant Potential, Physico-chemical, and Sensory Attributes of Cookies Supplemented with Mosambi Peel Extract. Issue 3 (2nd July 2016) - Imran, M.; Butt, M. S.; Iqbal, M. J.; Gilani, S. A.; Basharat, S.; Saeed, F.; Suleria, H. A. R.
ABSTRACT: The core objective of the present investigation was to isolate and quantify antioxidants from mosambi (sweet orange) peel. In the proposed research, different solvents were used for the extraction of antioxidants from mosambi peel. Among these solvents, ethanol resulted in better antioxidant yield compared to aqueous extract. Ethanolic extract of mosambi peel showed higher total phenolic contents (19.3 ± 0.3 mg/g) as compared to aqueous extracts (18.2 ± 0.04 mg/g). Considering the safety health concern, aqueous extract of mosambi peel was incorporated in cookies at different concentrations of 1%, 2%, and 3%, and further subjected to physico-chemical and sensory attributes. Proximate composition (moisture, crude protein, crude fat, crude fiber, ash, and niitrogen-free extract (NFE) contents) of fortified cookies varied non-significantly. However, sensory evaluation rated aqueous extract of mosambi peel (2%) with better hedonic response. Mosambi peel antioxidants have a great potential to be used in various functional foods and the ability to improve storage stability.